Hepatitis B virus infection among pregnant women on antenatal visits: rapid tests or ELISA? (2021)
Background: Hepatitis B virus (HBV) infection is a global public health challenge with over 360 million people infected worldwide, and is one of the leading causes of death worldwide. The hepatitis B surface antigen (HBSAg) is the most important marker for HBV screening, and HBSAg rapid screening test methods are the most widely used compared with the enzyme-linked immunosorbent assay (ELISA) and nucleic acid testing methods. The objectives of this study are to evaluate the comparative efficacy of rapid test kits and ELISA for HBV screening among pregnant women on antenatal visits and to screen for other HBV serological markers among HBsAg positive patients. Methodology: This is a cross-sectional study of 172 pregnant women who were recruited consecutively on their first antenatal visit at the University College Hospital, Ibadan, Nigeria between November 2018 and February 2019. All participants were screened for HBsAg using both rapid immunochromatographic test (ICT) and ELISA techniques. HBsAg negative samples were further screened for anti-HBeAg/Ab, anti-HBcAg and anti-HBs by ELISA. Socio-demographic data of the participants were obtained using a semi-structured questionnaire, and data were analyzed using EPI INFO 7.2 statistical software. Results: The prevalence rate of HBsAg among pregnant women in this study was 10.5% (18/172). The sensitivity, specificity, accuracy, positive predictive value (PPV) and the negative predictive value (NPV) of the rapid ICT kit were 72.2%, 97.4%, 94.8%, 76.5% and 96.8% respectively. Level of education, previous history of sexually transmitted infections (STIs) and previous positive HBV results were significantly associated with HBsAg seropositivity. Majority of the pregnant women (66.9%) tested negative to all the serological markers. Conclusion: The low efficacy of rapid ICT kits compared to ELISA justifies the need to develop a safer antenatal screening strategy for HBV by combining the use of the less sensitive rapid screening techniques with the more sensitive ELISA method to limit vertical transmission of hepatitis B virus.